ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI JAGUNG DI DESA BANGE KECAMATAN SANGGAU LEDO KABUPATEN BENGKAYANG - Ellyta Ellyta; Hironimus Hironimus (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The objective of the research was to analyze the factors which affect production of corn (Zea Mays L) in in Bange Village, Sanggau Ledo District, Bengkayang Regency. The population was set in purposive sampling on farmers group in the number of farmers about 225 farmers. The total sample took by 34 respondents. The data analyzed in multiple linier regression analysis. In partial could be concluded that the number of the use of seeds, the number of the use of urea fertilizer, the number of the use of NPK fertilizer 15:15:15, and the number of labour outside of family had real impact to corn production. Simultaneously could be inferred that the number of the use of seeds, the amount of urea fertilizer), the amount of SP-36 fertilizer, the number of the use of NPK fertilizer 15:15:15, the number of the use of manure, the amount of pesticide use, the use of family labour and the number of labour outside of family influential real on the corn production.